Altered Spatiotemporal Dynamics of the Resting Brain in Mild Cognitive Impairment with Lewy Bodies - Lamoš, Martin; Morávková, Ivona; Ondráček, David; Bočková, Martina; Rektorová, Irena (Movement disorders, 2021)
BACKGROUND: Electrophysiological markers of prodromal dementia with Lewy bodies were described in the spectral domain. The sub-second temporal resolution may provide additional information. OBJECTIVE: To evaluate electroencephalography (EEG) microstates in patients with mild cognitive impairment with Lewy bodies and to assess the association between their temporal dynamics and the spectral marker. METHODS: Temporal parameters of microstates were compared between 21 patients with mild cognitive impairment with Lewy bodies and 21 healthy controls. The dominant alpha frequency was correlated with microstate parameters. RESULTS: Microstates A-D showed higher occurrence in the patient group. Microstate B additionally revealed shorter mean duration and increased time coverage; its occurrence correlated with the dominant alpha frequency in the patient group. CONCLUSIONS: Temporal dynamics of all EEG microstates were altered in medication-naïve subjects with prodromal dementia with Lewy bodies. Longitudinal follow-up may reveal how EEG microstates reflect progression of brain function deficits and effects of treatment manipulations. © 2021 International Parkinson and Movement Disorder Society.
Keywords: prodromal DLB; demence s Lewyho tělísky; Cognitive Dysfunction; Electroencephalography; elektroencefalografie; mozek; synucleinopathy; EEG microstates; Lewyho tělíska; Brain; Humans; Lewy Bodies; Rest; odpočinek; kognitivní dysfunkce; medication-naïve; MCI-LB; Lewy Body Disease; lidé